In vivo protein crystallization opens new routes in structural biology - Koopmann, Rudolf; Epp, Sascha W.; Erk, Benjamin Michael Dieter; Foucar, Lutz Michael; Kassemeyer, Stephan; Lomb, Lukas; Rolles, Daniel; Rudek, Benedikt; Rudenko, Artem; Schlichting, Ilme; Shoeman, Robert L.; Ullrich, Joachim (Nature methods, 2012)
Protein crystallization in cells has been observed several times in nature. However, owing to their small size these crystals have not yet been used for X-ray crystallographic analysis. We prepared nano-sized in vivo-grown crystals of Trypanosoma brucei enzymes and applied the emerging method of free-electron laser-based serial femtosecond crystallography to record interpretable diffraction data. This combined approach will open new opportunities in structural systems biology.
Gesehen am 18.09.2018